Mimicking the Regulation Step of Fe‐Monooxygenases: Allosteric Modulation of FeIV‐Oxo Formation by Guest Binding in a Dinuclear ZnII–FeII Calix[6]arene‐Based Funnel Complex. Issue 12 (27th January 2017) - Ségaud, Nathalie; De Thomasson, Constance; Daverat, Caroline; Sénéchal‐David, Katell; Dos Santos, Amandine; Steinmetz, Vincent; Maître, Philippe; Rebilly, Jean‐Noël; Banse, Frédéric; Reinaud, Olivia
Abstract: A heteroditopic ligand associated with a calix[6]arene scaffold bearing a tris(imidazole) coordinating site at its small rim and an amine/pyridine ligand at its large rim has been prepared, and its regioselective coordination to Zn II at the small rim and Fe II in the amine/pyridine ligand has been achieved. The heterodinuclear complex obtained displays an overall cone conformation capped by the tris(imidazole)Zn II moiety and bears a non‐heme Fe II complex at its base. Each of the metal centers exhibits one labile position, allowing the coordination inside the cavity of a guest alkylamine at Zn II and the generation of reaction intermediates (Fe III (OOH) and Fe IV O) at the large rim. A dependence between the chain length of the encapsulated alkylamine and the distribution of Fe III (OOH) intermediates and Fe III (OMe) is observed. In addition, it is shown that the generation of the Fe IV O intermediate is enhanced by addition of the alkylamine guest. Hence, this supramolecular system gathers the three levels of reactivity control encountered in oxidoreductases: i) control of the Fe II redox properties through its first coordination sphere, allowing us to generate high valent reactive species; ii) control of guest binding through a hydrophobic funnel that drives its alkyl chain next to the reactive iron complex, thus mimicking the binding pocket of natural systems; iii) guest‐modulated reactivity of the Fe II center towards oxidants. Abstract : The host with the most : A heteroditopic calix[6]arene scaffold bearing a tris(imidazole) coordinating site at its small rim and an amine/pyridine ligand at its large rim has been prepared, and its regioselective coordination to Zn II at the small rim and Fe II in the amine/pyridine ligand has been achieved. Each of the metal centers exhibits one labile position, allowing the coordination of a guest alkylamine inside the cavity at Zn II and the generation of reaction intermediates (Fe III (OOH) and Fe IV O) at the large rim (see figure).